Attraction or Repulsion? London Dispersion Forces Control Azobenzene Switches. Issue 45 (9th September 2015) - Schweighauser, Luca; Strauss, Marcel A.; Bellotto, Silvia; Wegner, Hermann A.
Abstract: Large substituents are commonly seen as entirely repulsive through steric hindrance. Such groups have additional attractive effects arising from weak London dispersion forces between the neutral atoms. Steric interactions are recognized to have a strong influence on isomerization processes, such as in azobenzene‐based molecular switches. Textbooks indicate that steric hindrance destabilizes the Z isomers. Herein, we demonstrate that increasing the bulkiness of electronically equal substituents in the meta‐position decreases the thermal reaction rates from the Z to the E isomers. DFT computations revealed that attractive dispersion forces essentially lower the energy of the Z isomers. Abstract : London's calling : It is generally accepted that large alkyl substituents destabilize the Z isomer of double bonds. In the case of meta ‐substituted azobenzenes, it could be shown that the stability of the Z isomer increases as the size of the substituent grows. Computations show that the enhancement in stability is based on intramolecular London dispersion forces, which compete with steric hindrance in the Z isomers.